Pragmatic vs explanatory trials: the Pragmascope tool to help measure differences in protocols of mental health randomized controlled trials - Tosh, Graeme (Les Laboratoires Servier, 2011)
In the pragmatic-explanatory continuum, a randomized controlled trial (RCT) can at one extreme investigate whether a treatment could work in ideal circumstances (explanatory), or at the other extreme, whether it would work in everyday practice (pragmatic). How explanatory or pragmatic a study is can have implications for clinicians, policy makers, patients, researchers, funding bodies, and the public. There is an increasing need for studies to be open and pragmatic; however, explanatory trials are also needed. The previously developed Pragmatic-explanatory continuum indicator summary (PRECIS) was adapted into the Pragmascope tool to assist mental health researchers in designing RCTs, taking the pragmatic-explanatory continuum into account. Ten mental health trial protocols were randomly chosen and scored using the tool by three independent raters. Their results were compared for consistency and the tool was found to be reliable and practical. This preliminary work suggests that evaluating different domains of an RCT at the protocol level is useful, and suggests that using the Pragmascope tool presented here might be a practical way of doing this.